Low-stress anti-coking alternating laminated film for intake and exhaust valves of engine and preparation method of low-stress anti-coking alternating laminated film

By adopting a multi-layer alternating structure of CrN, CrAlN and TiO2 on the engine inlet and exhaust valves, the stress balance in the film is achieved, and the problem of coking at high temperatures is solved, and the anti-coking performance and stability are improved.

CN119900026AActive Publication Date: 2025-04-29XI AN JIAOTONG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510050384.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The engine inlet and exhaust valves are prone to coking in high-temperature working environments, and the existing coatings have problems of decreasing adhesion and peeling under high-temperature oxidation and mechanical loads.

Method used

Using a multi-layer alternating structure of chromium nitride (CrN), chromium aluminum nitride (CrAlN) and titanium dioxide (TiO2), the internal stress balance of the film in a high-temperature environment is achieved through multi-layer stress balance design.

Benefits of technology

It significantly reduces the internal stress level of the film, improves the anti-coking performance and stability of the film, extends the service life, and optimizes the overall performance and emission control of the engine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900026A_ABST
    Figure CN119900026A_ABST
Patent Text Reader

Abstract

The invention discloses a low-stress anti-coking alternate laminated film for an intake and exhaust valve of an engine and a preparation method. The low-stress anti-coking alternate laminated film comprises a CrN film, a CrAlN film, a TiO2 film, a CrN film, a CrAlN film and a TiO2 film which are sequentially arranged on a substrate from bottom to top. According to the structure, through multiple times of alternate deposition of the CrN layer, the CrAlN layer and the TiO2 layer, the tensile stress and the compressive stress in the thin film are effectively balanced, and stress concentration and thermal residual stress in the using process are remarkably reduced. The CrN layer is used as a bottom layer and a transition layer to enhance the adhesive force between the film and the substrate and between the layers; the CrAlN layer provides high hardness and high temperature resistance; and the TiO2 layer endows the film with excellent anti-coking performance. Through reasonable structural design and stress distribution control, the alternately laminated film shows excellent anti-coking and anti-oxidation performance in a high-temperature aerobic environment, and the service life of an intake valve and an exhaust valve is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface engineering, and in particular to a low-stress anti-coking alternately laminated film for engine intake and exhaust valves and a preparation method thereof. Background Art

[0002] As a type of internal combustion engine, the engine is widely used in industries such as industry, transportation, and power generation. During the operation of the engine, the intake and exhaust valves are key components that control the flow of gas into and out of the combustion chamber. They work in a high-temperature, high-pressure, and corrosive gas environment, and are subject to extreme thermal and mechanical loads. Especially during the exhaust process, the exhaust valve is directly exposed to high-temperature exhaust gas, with temperatures reaching 600 to 800°C, while the intake valve is relatively low, about 300 to 400°C. This high-temperature environment causes severe coking and deposition on the surface of the material. Long-term carbon deposition will not only increase airflow resistance and reduce engine performance, but may also cause valve temperatures to be too high, accelerating oxidation and mechanical fatigue, seriously affecting the engine's operating efficiency and service life.

[0003] In recent years, due to the complexity of high temperature, high oxidation and dynamic thermomechanical environment of engine intake and exhaust valves, higher requirements have been put forward for the anti-oxidation and anti-coking performance of surface coatings. Studies have shown that single-layer coatings often show problems of decreased adhesion and coating peeling due to the combined effects of thermal stress and high-temperature oxidation. Patent CN114959574A points out that CrAlN coatings are prone to decomposition under high temperature conditions to generate wurtzite AlN and cubic Cr structures, accompanied by the loss of nitrogen. This microstructural change directly weakens the hardness and wear resistance of the coating, significantly limiting its long-term application in engine intake and exhaust valves. In order to improve the shortcomings of single-layer coatings, double-layer coating technology has been proposed. Patent CN117344274A describes a TiN transition layer and AlTiN functional layer alternately stacked coating prepared by arc ion plating process, which improves the adhesion of the coating by reducing the interface stress. However, under the extreme dynamic conditions of the engine intake and exhaust valves, the double-layer coating still has the problem of interface stress mismatch, which may lead to delamination or cracking. In addition, patent CN109468614A proposes an Al2O3 / TiO2 nano-alternating layered coating based on atomic layer deposition technology, where the bottom layer of Al2O3 is used to block carbon penetration and the surface layer of TiO2 reduces the catalytic effect of carbon deposition. Although the double-layer coating shows improvements in anti-oxidation and anti-coking, its interface stability in complex dynamic thermomechanical environments still needs to be further optimized.

[0004] The coating prepared by the above method has not yet been able to completely solve the problem of coking of the engine intake and exhaust valves under high temperature working environment. Summary of the invention

[0005] In order to overcome the problem of engine intake and exhaust valves being prone to coking under the existing high-temperature working environment, the purpose of the present invention is to provide a low-stress anti-coking alternating laminated film for engine intake and exhaust valves and a preparation method, which prepares a multi-layer alternating structure of chromium nitride (CrN), chromium aluminum nitride (CrAlN) and titanium dioxide (TiO2), and through a multi-level stress balance design, fully utilizes the compressive stress characteristics of the CrN and CrAlN layers and the tensile stress characteristics of the TiO2 layer to achieve the internal stress balance of the film in a high-temperature environment. This low-stress design can effectively reduce the risk of film peeling under high-temperature oxidation and mechanical load, and significantly improve the anti-coking performance of the film, thereby providing an efficient solution for the long-term protection of engine intake and exhaust valves.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A low-stress anti-coking alternately laminated film for engine intake and exhaust valves comprises a CrN film, a CrAlN film, a TiO2 film, a CrN film, a CrAlN film and a TiO2 film which are sequentially arranged on a substrate from bottom to top.

[0008] Furthermore, the thickness of the CrN films is 0.2 to 0.5 μm;

[0009] The thickness of CrAlN films is 2 to 4 μm;

[0010] The thickness of TiO2 film is 50-150nm.

[0011] Furthermore, the total thickness of the low-stress anti-coking alternately laminated film is 5 to 9 μm.

[0012] A method for preparing a low-stress anti-coking alternately laminated film for an engine intake and exhaust valve comprises the following steps:

[0013] A CrN film is first deposited on the substrate surface, a CrAlN film is deposited on the CrN film, and a TiO2 film is prepared on the CrAlN film;

[0014] A CrN film is deposited on a TiO2 film, a CrAlN film is deposited on a CrN film, and a TiO2 film is prepared on a CrAlN film to obtain a low-stress anti-coking alternating laminated film for an engine intake and exhaust valve.

[0015] Furthermore, the thickness of the CrN films is 0.2 to 0.5 μm;

[0016] The thickness of CrAlN films is 2 to 4 μm;

[0017] The thickness of TiO2 films is 50 to 150 nm;

[0018] The total thickness of the low stress anti-coking alternately laminated film is 5 to 9 μm.

[0019] Furthermore, the preparation process of CrN film is as follows: using Cr target, the multi-arc ion plating process parameters are: CrAl target arc current is 70-100A, deposition bias is 100-300V; the chamber pressure is 1-5Pa, the nitrogen flow rate is 1300-1500sccm, and the deposition temperature is about 350°C.

[0020] Furthermore, the CrAl target is an alloy target in which the atomic percentage of Cr is 60% to 75%.

[0021] Furthermore, the preparation process of CrAlN film is as follows: using CrAl target, the multi-arc ion plating process parameters are: arc current is 70-100A, bias voltage is 50-80V, chamber pressure is 1-5Pa, nitrogen flow rate is 1300-1500sccm, and deposition temperature is about 350°C.

[0022] Furthermore, the process for preparing the TiO2 thin film is as follows: titanium isopropoxide is used as a titanium source precursor and hydrogen peroxide is used as an oxygen source, nitrogen is used as a purge gas in a single cycle of the atomic layer deposition process, and the times for titanium source precursor injection, nitrogen purge, oxygen source injection, and nitrogen purge are 1 to 2 s, 25 to 35 s, 0.1 to 0.3 s, and 20 to 35 s, respectively; the total number of cycles of the atomic layer deposition process is 2000 times.

[0023] Furthermore, the temperature of the titanium source precursor is 70-90° C., the temperature of the coating area is 200-250° C., the background vacuum is lower than 50 mtorr, and the nitrogen purge working pressure is 100-200 mtorr.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] The low stress anti-coking alternating laminated film in the present invention is designed for the engine intake and exhaust valves. By rationally designing the alternating laminated structure of the film, the CrN, CrAlN and TiO2 layers are alternately arranged, which effectively regulates the distribution of stress in the film and significantly reduces the internal stress level of the film. In the alternating laminated film structure, the CrAlN layer usually generates compressive stress during the deposition process due to its high hardness and strong high temperature resistance. This compressive stress helps to improve the hardness and wear resistance of the film, reduce thermal fatigue and wear in high temperature environments, and thus enhance the stability and durability of the film. In contrast, the TiO2 layer usually generates tensile stress during the deposition process due to its relatively brittleness. This tensile stress helps to improve the adhesion of the film to a certain extent, especially to improve the bonding strength between the TiO2 layer and the CrAlN layer, while enhancing the anti-coking performance of the film. By arranging the CrN layer as a transition layer between the substrate and the CrAlN layer, and between the first layer of TiO2 and the second layer of CrAlN, the stress distribution of the film is further optimized. The CrN layer can effectively alleviate the stress concentration caused by the difference in thermal expansion coefficient between the substrate and the hard CrAlN layer, and also adjust the tensile stress of the TiO2 layer, thereby achieving a balanced distribution of stress. This reasonable stress ratio not only avoids brittle cracking or peeling of the film under high temperature conditions, but also improves the overall fatigue resistance of the film and prolongs its service life. In a high-temperature, aerobic working environment, the high hardness and high-temperature resistance of the CrAlN layer effectively protect the intake and exhaust valves from wear and oxidation erosion during high-temperature combustion. The TiO2 layer exerts its excellent anti-coking function, significantly reduces carbon accumulation, keeps the valve surface clean, thereby ensuring smooth airflow and improving engine combustion efficiency and power output. The low-stress design of the alternating laminated film optimizes the bonding force between the film and the substrate, reduces the risk of peeling and wear, and reduces the maintenance and replacement frequency of the film. The low-stress anti-coking alternating laminated film of the present invention not only improves the anti-coking ability of the intake and exhaust valves under high temperature conditions, but also significantly prolongs the service life of the film through reasonable stress design, optimizes the overall performance and emission control of the engine, and helps diesel engines meet increasingly stringent environmental emission standards. The film has good compatibility with engine materials and does not affect the mechanical properties and structural integrity of the intake and exhaust valves, ensuring the stable operation of the engine under high temperature and high pressure. It has broad application prospects and significant economic benefits.

[0026] The method of the present invention combines the multi-arc ion plating process and the atomic layer deposition technology. First, the multi-arc ion plating process is used to deposit the CrN transition layer and the CrAlN hard layer on the surface of the intake and exhaust valves in sequence. The CrN layer enhances the adhesion between the film and the substrate and further optimizes the stress distribution of the film. The CrAlN layer significantly improves the hardness and wear resistance of the film. The ALD technology is used to uniformly deposit the TiO2 nanofilm on the surface of the CrAlN layer. The TiO2 layer can effectively inhibit the accumulation of coking materials and exhibit excellent anti-oxidation performance under high temperature environment.

[0027] Furthermore, the thickness of the TiO2 layer is between 50 and 150 nm to ensure the high temperature anti-coking effect and the overall stability of the film.

[0028] Furthermore, in the present invention, the deposition temperature of the CrN and CrAlN layers is controlled at 350° C. to ensure the compactness and stability of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the structure of the engine intake and exhaust valve test piece, where (a) is a schematic diagram of the intake valve; (b) is a schematic diagram of the exhaust valve;

[0030] Figure 2 Schematic diagram of the hierarchical structure of low stress alternating stacked films;

[0031] Figure 3 This is a comparison chart of the mass changes of the uncoated and alternately laminated film test pieces before and after the anti-coking experiment;

[0032] Figure 4 Comparison chart of film stress changes. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0034] The method for preparing a low-stress anti-coking alternating laminated film for an engine intake and exhaust valve of the present invention combines two processes, namely, multi-arc ion plating and atomic layer deposition. First, an intermediate layer is prepared on the surface of a substrate by multi-arc ion plating, wherein the intermediate layer includes a CrN film and a CrAlN film, and then a high-quality TiO2 film with an anti-coking function is prepared on the surface of the CrAlN film by atomic layer deposition. Then, the above steps are repeated to alternately deposit CrN, CrAlN and TiO2 films, thereby obtaining an alternating laminated film with low-stress anti-coking performance on the substrate.

[0035] Preferably, the method for preparing the alternating laminated film specifically comprises the following steps:

[0036] 1) grinding, polishing, cleaning and drying the substrate in sequence to make the substrate surface clean to ensure the initial adhesion of the film; then firstly depositing a CrN film with a thickness of 0.2 to 0.5 μm on the clean substrate surface, and then depositing a CrAlN film thereon to obtain a substrate plated with CrAlN;

[0037] 2) The CrAlN-plated substrate is cleaned and then dried.

[0038] 3) A TiO2 film is prepared on the surface of the substrate coated with CrAlN by atomic layer deposition to form a CrAlN / TiO2 alternating laminated film. Then, the above steps 2) to 3) are repeated to alternately deposit CrN, CrAlN and TiO2 films, thereby obtaining a low-stress anti-coking alternating laminated film for engine intake and exhaust valves on the substrate.

[0039] Preferably, in step 1), the ground and polished substrate is ultrasonically cleaned with anhydrous ethanol for 10 minutes and then blown dry with nitrogen.

[0040] Preferably, in step 1), the multi-arc ion plating process parameters for preparing a CrN film with a thickness of 0.1 to 0.5 μm using a pure Cr target are: arc current of 70 to 100 A, deposition bias of 100 to 300 V; chamber pressure of 1 to 5 Pa, nitrogen flow rate of 1300 to 1500 sccm, and deposition temperature of approximately 350°C.

[0041] Preferably, in the step 1), the multi-arc ion plating process parameters for preparing a CrAlN film with a thickness of 3 to 4 μm using a CrAl target are: arc current of 70 to 100 A, bias voltage of 50 to 80 V, chamber pressure of 1 to 5 Pa, nitrogen flow rate of 1300 to 1500 sccm, and deposition temperature of approximately 350°C.

[0042] Preferably, the CrAl target is an alloy target with an atomic percentage of Cr of 60% to 75%.

[0043] Preferably, in the step 3), titanium isopropoxide is used as the titanium source precursor and hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 24% to 35%) is used as the oxygen source to prepare a TiO2 film with a thickness of 50 to 150 nm; nitrogen is used as the purge gas in a single cycle of the atomic layer deposition process, and the times for titanium source precursor injection, nitrogen purge, oxygen source injection, and nitrogen purge are 1 to 2 s, 25 to 35 s, 0.1 to 0.3 s, and 20 to 35 s, respectively; the total number of cycles of the atomic layer deposition process is 2000 times.

[0044] Preferably, in step 3), the temperature of the titanium source precursor is 70-90° C., the temperature of the coating zone is 200-250° C., the background vacuum is lower than 50 mtorr, and the nitrogen purge working pressure is 100-200 mtorr.

[0045] In the present invention, before each deposition of the TiO2 layer, the surface of the lower CrAlN layer is cleaned and dried to improve the adhesion of the TiO2 layer.

[0046] In the present invention, the thickness of the TiO2 layer is between 50 and 150 nm to ensure the high temperature anti-coking effect and the overall stability of the film.

[0047] In the present invention, the deposition temperature of the CrN and CrAlN layers is controlled at 350° C. to ensure the compactness and stability of the film.

[0048] The film in the present invention is formed by alternatingly stacking CrN layers, CrAlN layers and TiO2 layers on a substrate. The above-mentioned alternatingly stacked film has excellent high-temperature anti-stripping and anti-coking properties, and can be used on the intake and exhaust valves of the engine to passivate the surface of the exhaust valve and protect against high-temperature coking. The film has high interface bonding strength, which can effectively reduce the stress concentration of the film in a high-temperature working environment, improve the stability and anti-coking performance, and thus extend the service life of the film.

[0049] The alternatingly laminated films of the present invention improve structural stability and anti-stripping performance through a balanced design of compressive stress and tensile stress under high temperature environment, thereby effectively inhibiting coking accumulation and significantly improving the durability and operating efficiency of the engine.

[0050] The method of the present invention combines the multi-arc ion plating process and the atomic layer deposition technology. First, the multi-arc ion plating process is used to deposit the CrN transition layer and the CrAlN hard layer on the surface of the intake and exhaust valves in sequence. The CrN layer enhances the adhesion between the film and the substrate and further optimizes the stress distribution of the film. The CrAlN layer significantly improves the hardness and wear resistance of the film. The ALD technology is used to uniformly deposit the TiO2 nanofilm on the surface of the CrAlN layer. The TiO2 layer can effectively inhibit the accumulation of coking materials and exhibit excellent anti-oxidation performance under high temperature environment.

[0051] A key innovation of the present invention is the low stress design of the film structure. By alternately depositing CrN, CrAlN and TiO2 layers and introducing the CrN layer as a transition layer, the internal stress of the film can be effectively adjusted. The CrN layer, as a transition layer, alleviates the stress concentration caused by the difference in physical properties between the different layers of materials, and avoids the film from peeling off or cracking due to excessive internal stress. In addition, the CrAlN layer further improves the film's resistance to high temperature peeling and provides a stable substrate for the TiO2 layer, ensuring that the TiO2 layer maintains good adhesion in a high temperature oxygen environment.

[0052] The final alternating laminated film structure is "substrate-CrN-CrAlN-TiO2-CrN-CrAlN-TiO2", which not only has good anti-coking performance, but also significantly improves the durability and reliability of the intake and exhaust valves in high temperature environments. The low-stress design ensures that the film works stably under high-temperature engine operating conditions, avoiding film peeling or damage due to excessive internal stress, thereby extending the service life of the engine's metal structural parts and improving its safety and reliability in harsh working environments.

[0053] Example 1

[0054] (I) Alternating stacked thin film preparation experiment

[0055] See also Figure 1 (a) and (b) are test pieces of intake and exhaust valves, which are flat-top valve head type intake and exhaust valves. The intake valve has an outer diameter B1 of 23 mm, a total height A of 61 mm, and a thickness C of 5 mm. The exhaust valve has an outer diameter B2 of 20 mm, a total height A of 61 mm, and a thickness C of 5 mm.

[0056] See also Figure 2 , which is a schematic diagram of the structure of the "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" low stress anti-coking alternating stacked film prepared in the experiment. The film includes a CrN film, a CrAlN film, a TiO2 film, a CrN film, a CrAlN film and a TiO2 film arranged on a substrate from bottom to top.

[0057] The low stress anti-coking alternating laminated film is prepared on the intake and exhaust valve substrate. The specific process is as follows:

[0058] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0059] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment and evacuate it to less than 5.0×10 - 3 Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the gas inlet valve, fill in 400sccm of argon, set the target bias voltage to 800V and perform glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V, 300V and perform Ar + Bombardment cleaning (30 min in total) cleans the substrate surface.

[0060] Then, the CrN transition layer was prepared by introducing nitrogen gas with a purity of 99.99%, arc current of the Cr target of 100A, bias voltage of 100V, nitrogen flow rate of 1450sccm, chamber pressure of 3Pa, process time of about 18min, and deposition temperature of 350°C. The deposition thickness of the obtained metal CrN transition layer was 0.4μm.

[0061] Then, the CrAlN film was prepared by introducing nitrogen gas with a purity of 99.99%, arc current of 90A for the CrAl target (atomic percentage of 70% Cr: 30% Al), bias voltage of 60V, nitrogen flow rate of 1450sccm, chamber pressure of 4Pa, process time of about 120min, deposition temperature of 350℃, and deposition thickness of 3.5μm. Thus, a substrate coated with CrAlN was obtained.

[0062] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0063] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0064] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 200℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 70℃), hydrogen peroxide (30% H2O2 aqueous solution by mass fraction) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve. The working pressure during the high-purity nitrogen purge is 200mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1.5s, 30s, 0.2s, and 20s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 150nm on the surface of the substrate coated with CrAlN.

[0065] Step 5: Repeat steps 1 to 4 to obtain a low-stress anti-coking alternating laminated film with a structure of "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" on the surface of the substrate.

[0066] (II) Film anti-coking protection test

[0067] In order to test the anti-coking performance of the film, the test piece with the alternating laminated film was placed in a circular tube with a diameter of 30 mm and faced the flow direction of the hydrocarbon fuel. The experiment adjusted the flow rate of the fuel through a flow control device. After the fuel was output by the delivery device, it was first heated through the preheating section and then entered the circular tube of the experimental section. The test piece was then subjected to an anti-coking protection experiment for 1 hour at a temperature of 800K. In the experimental section pipeline, the flow channel of the hydrocarbon fuel simulates the flow channel shape of the engine intake and exhaust valves. This setting is intended to simulate the fuel flow and heat treatment process of the engine intake and exhaust valves in actual work, so as to evaluate the anti-coking performance of the alternating laminated film under high temperature and high pressure environment. Before and after the experiment, the mass changes of the test pieces without coating and with alternating laminated films were measured.

[0068] See also Figure 3 The weight changes of the test pieces before and after the anti-coking experiment were compared. The results showed that under the same test conditions, the weight increase of the test pieces with alternating laminated films was 0.1 mg, while the weight increase of the test pieces without coating protection was 1.0 mg, which reflects the anti-coking effect of the alternating laminated films.

[0069] (III) Film anti-peeling test

[0070] The test piece coated with the alternating laminated film was heated to 850°C in a tube furnace at a heating rate of 8°C / min, kept at this temperature for 1.5 hours, and then cooled to room temperature with the furnace to complete the annealing. The sample was annealed in air (850°C, 1.5 hours). The observation results showed that the alternating laminated film on the surface of the sample remained intact without damage or peeling. This result shows that the alternating laminated film has a good protective effect on the substrate and effectively improves the anti-coking performance of the substrate.

[0071] (IV) Stress test experiment before and after coating

[0072] The internal stress of substrates under three different treatment conditions was measured using the FST2000 thin film stress tester (curvature method). The experimental samples included: uncoated substrates, substrates coated with "CrN-CrAlN-TiO2" alternating stacked films, and substrates coated with "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" alternating stacked films. First, the film thickness of each sample was measured using an ellipsometer to ensure that the thickness of each film met the predetermined requirements. Then, stress tests were performed on uncoated substrates, substrates coated with single-layer alternating stacked films, and substrates coated with multiple layers of alternating stacked films, and the baseline data was recorded and compared.

[0073] See also Figure 4, the test results show that the internal stress of the uncoated substrate is higher, while the internal stress of the substrate coated with the "CrN-CrAlN-TiO2" alternating stacked film is reduced, indicating that the single-layer alternating stacked film can effectively relieve internal stress. Furthermore, the substrate coated with the "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" multi-layer alternating stacked film showed the most significant reduction in internal stress, indicating that the structure disperses the internal stress more effectively through the alternating stacking design. All samples were also subjected to high-temperature treatment at 850℃ for 1.5h and cooled with the furnace. The stress test results after high-temperature treatment showed that the internal stress of the film changed little, indicating that the low-stress design has good stability in high-temperature environments.

[0074] Example 2

[0075] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0076] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment and evacuate it to less than 5.0×10 - 3 Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the gas inlet valve, fill in 400sccm of argon, set the target bias voltage to 800V and perform glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V, 300V and perform Ar + Bombardment cleaning (30 min in total) cleans the substrate surface.

[0077] Then prepare the CrN transition layer: nitrogen with a purity of 99.99%, arc current of Cr target 70A, deposition bias 300V, nitrogen flow rate 1300sccm, chamber pressure 2Pa, process time about 15min, deposition temperature 350℃, the deposition thickness of the obtained metal CrN transition layer is 0.2μm.

[0078] Then, CrAlN film was prepared: nitrogen gas with a purity of 99.99% was introduced, arc current of CrAl target (atomic percentage of 60% Cr: 40% Al) was 70A, bias voltage was 60V, nitrogen flow rate was 1300sccm, chamber pressure was 1Pa, process time was about 120min, deposition temperature was 350℃, and deposition thickness of CrAlN film was 4μm. Thus, a substrate coated with CrAlN was obtained.

[0079] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0080] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0081] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 200℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 70℃), hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 24%) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve, and the working pressure during high-purity nitrogen purge is 150mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1.5s, 15s, 0.3s, and 20s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 100nm on the surface of the substrate coated with CrAlN.

[0082] Step 5: Repeat steps 1 to 4 to obtain a low-stress anti-coking alternating laminated film with a structure of "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" on the surface of the substrate.

[0083] After testing, the internal stress of the alternately stacked film prepared in Example 3 was 83 MPa. The film anti-peeling test results showed that the film on the surface of the sample did not break or peel off.

[0084] Example 3

[0085] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0086] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment and evacuate it to less than 5.0×10 - 3 Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the gas inlet valve, fill in 400sccm of argon, set the target bias voltage to 800V and perform glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V, 300V and perform Ar + Bombardment cleaning (30 min in total) cleans the substrate surface.

[0087] Then prepare the CrN transition layer: nitrogen with a purity of 99.99%, arc current of Cr target 100A, bias voltage 150V, nitrogen flow rate 1500sccm, chamber pressure 5Pa, process time about 20min, deposition temperature 350℃, the deposition thickness of the obtained metal CrN transition layer is 0.5μm.

[0088] Then, CrAlN film was prepared: nitrogen gas with a purity of 99.99% was introduced, arc current of CrAl target (atomic percentage of 75% Cr: 25% Al) was 80A, bias voltage was 50V, nitrogen flow rate was 1400sccm, chamber pressure was 5Pa, process time was about 100min, deposition temperature was 350℃, and deposition thickness of CrAlN film was 3μm. Thus, a substrate coated with CrAlN was obtained.

[0089] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0090] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0091] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 200℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 70℃), hydrogen peroxide (35% H2O2 aqueous solution by mass fraction) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve, and the working pressure during high-purity nitrogen purge is 100mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1.5s, 15s, 0.2s, and 30s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 50nm on the surface of the substrate coated with CrAlN.

[0092] Step 5: Repeat steps 1 to 4 to obtain a low-stress anti-coking alternating laminated film with a structure of "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" on the surface of the substrate.

[0093] After testing, the internal stress of the alternately stacked film prepared in Example 3 was 90 MPa. The film anti-peeling test results showed that the film on the surface of the sample did not break or peel off.

[0094] Example 4

[0095] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0096] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment and evacuate it to less than 5.0×10 - 3 Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the gas inlet valve, fill in 400sccm of argon, set the target bias voltage to 800V and perform glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V, 300V and perform Ar + Bombardment cleaning (30 min in total) cleans the substrate surface.

[0097] Then prepare the CrN transition layer: nitrogen with a purity of 99.99%, arc current of Cr target 80A, bias voltage 300V, nitrogen flow rate 1400sccm, chamber pressure 5Pa, process time about 10min, deposition temperature 350℃, the deposition thickness of the obtained metal CrN transition layer is 0.2μm.

[0098] Then, CrAlN film was prepared: nitrogen gas with a purity of 99.99% was introduced, arc current of CrAl target (atomic percentage of 65% Cr: 35% Al) was 70A, bias voltage was 70V, nitrogen flow rate was 1500sccm, chamber pressure was 3Pa, process time was about 90min, deposition temperature was 350℃, and deposition thickness of CrAlN film was 2.5μm. Thus, a substrate coated with CrAlN was obtained.

[0099] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0100] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0101] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 200℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 70℃), hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 27%) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve, and the working pressure during high-purity nitrogen purge is 200mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1.5s, 15s, 0.1s, and 20s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 80nm on the surface of the substrate coated with CrAlN.

[0102] Step 5: Repeat steps 1 to 4 to obtain a low-stress anti-coking alternating laminated film with a structure of "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" on the surface of the substrate.

[0103] After testing, the internal stress of the alternately stacked film prepared in Example 4 was 87 MPa. The film anti-peeling test results showed that the film on the surface of the sample did not break or peel off.

[0104] Example 5

[0105] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0106] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment and evacuate it to less than 5.0×10 - 3 Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the gas inlet valve, fill in 400sccm of argon, set the target bias voltage to 800V and perform glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V, 300V and perform Ar + Bombardment cleaning (30 min in total) cleans the substrate surface.

[0107] Then prepare the CrN transition layer: nitrogen with a purity of 99.99%, arc current of Cr target 70A, deposition bias 250V, nitrogen flow rate 1350sccm, chamber pressure 4Pa, process time about 18min, deposition temperature 350℃, the deposition thickness of the obtained metal CrN transition layer is 0.3μm.

[0108] Then, the CrAlN film was prepared by introducing nitrogen gas with a purity of 99.99%, arc current of 100A for the CrAl target (atomic percentage of 60% Cr: 40% Al), bias voltage of 80V, nitrogen flow rate of 1350sccm, chamber pressure of 2Pa, process time of about 80min, deposition temperature of 350℃, and deposition thickness of 2μm. Thus, a substrate coated with CrAlN was obtained.

[0109] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0110] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0111] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 220℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 90℃), hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 27%) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve, and the working pressure during high-purity nitrogen purge is 100mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1s, 25s, 0.3s, and 35s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 50nm on the surface of the substrate coated with CrAlN.

[0112] Step 5: Repeat steps 1 to 4 to obtain a low-stress anti-coking alternating laminated film with a structure of "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" on the surface of the substrate.

[0113] Example 6

[0114] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0115] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment and evacuate it to less than 5.0×10 - 3Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the gas inlet valve, fill in 400sccm of argon, set the target bias voltage to 800V and perform glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V, 300V and perform Ar + Bombardment cleaning (30 min in total) cleans the substrate surface.

[0116] Then, the CrN transition layer was prepared by introducing nitrogen gas with a purity of 99.99%, arc current of the Cr target of 90A, deposition bias of 200V, nitrogen flow rate of 1500sccm, chamber pressure of 1Pa, process time of about 20min, and deposition temperature of 350°C. The deposition thickness of the obtained metal CrN transition layer was 0.4μm.

[0117] Then, CrAlN film was prepared: nitrogen gas with a purity of 99.99% was introduced, arc current of CrAl target (atomic percentage of 70% Cr: 30% Al) was 70A, bias voltage was 50V, nitrogen flow rate was 1500sccm, chamber pressure was 1Pa, process time was about 90min, deposition temperature was 350℃, and deposition thickness of CrAlN film was 2.5μm. Thus, a substrate coated with CrAlN was obtained.

[0118] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0119] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0120] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 250℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 80℃), hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 27%) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve, and the working pressure during high-purity nitrogen purge is 150mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 2s, 35s, 0.1s, and 20s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 100nm on the surface of the substrate coated with CrAlN.

[0121] Step 5: Repeat steps 1 to 4 to obtain a low-stress anti-coking alternating laminated film with a structure of "CrN-CrAlN-TiO2-CrN-CrAlN-TiO2" on the surface of the substrate.

[0122] Comparative Example 1

[0123] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0124] Step 2: Directly prepare TiO2 thin film on the substrate using atomic layer deposition equipment.

[0125] The substrate is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 200℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 60℃), hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 27%) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve. The working pressure during high-purity nitrogen purge is 200mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1.5s, 30s, 0.1s, and 30s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 54nm on the surface of the substrate.

[0126] After testing, the internal stress of the single-layer TiO2 film prepared in Comparative Example 1 is 282MPa. The film anti-stripping test results show that the single-layer TiO2 film on the surface of the sample has a certain degree of damage and peeling, and can no longer play the anti-coking protection function.

[0127] Comparative Example 2

[0128] Step 1: Grind the substrate with 400, 800, 1200, and 2000 sandpaper in turn, then polish it with a polishing machine, and then use anhydrous ethanol to ultrasonically clean the ground and polished substrate for 15 minutes, then blow it dry with high-purity nitrogen (purity is 99.99%), and wipe the inner wall of the vacuum chamber with anhydrous ethanol.

[0129] Step 2: After sandblasting the substrate surface, place it in the vacuum coating equipment, evacuate to less than 5.0×10-3Pa, heat the substrate to 400℃ and keep it warm for 40min. Then open the air inlet valve, fill it with 400sccm of argon, set the target bias voltage to 800V for glow cleaning for 8min to remove the surface material of the target. Change the argon flow rate to 70sccm, adjust the substrate bias voltage to 500V and 300V in turn for Ar+ bombardment cleaning (30min in total) to clean the substrate surface.

[0130] Then, a CrN transition layer was prepared: nitrogen gas with a purity of 99.99% was introduced, the arc current of the Cr target was 90A, the bias voltage was 200V, the nitrogen flow rate was 1400sccm, the pressure in the chamber was 5Pa, the process time was about 25min, and the deposition thickness of the obtained metal CrN transition layer was 0.5μm.

[0131] Then, CrAlN film was prepared: nitrogen gas with a purity of 99.99% was introduced, arc current of CrAl target (atomic percentage of 70% Cr: 30% Al) was 60A, bias voltage was 40V, nitrogen flow rate was 1500sccm, pressure in the chamber was 3Pa, process time was about 100min, and deposition thickness of CrAlN film was 2.5μm. Thus, a substrate coated with CrAlN was obtained.

[0132] Step 3: Use anhydrous ethanol to ultrasonically clean the CrAlN-plated substrate for 15 minutes, and then blow dry with nitrogen.

[0133] Step 4: Prepare a TiO2 film on a CrAlN-coated substrate using an atomic layer deposition device.

[0134] The substrate coated with CrAlN is transferred to the coating chamber, and the chamber pressure is evacuated to 50mtorr. At the same time, the temperature is programmed to 200℃ and kept for 30min. Then, titanium isopropoxide is used as the titanium source precursor (temperature is 60℃), hydrogen peroxide (H2O2 aqueous solution with a mass fraction of 27%) is used as the oxygen source, and high-purity nitrogen (purity is 99.999%) is used as the purge gas. The flow rate of high-purity nitrogen is adjusted by a needle valve. The working pressure during the high-purity nitrogen purge is 200mtorr. In a single cycle of the atomic layer deposition process, the introduction time of the titanium source precursor, high-purity nitrogen, hydrogen peroxide, and high-purity nitrogen is 1.5s, 30s, 0.1s, and 30s respectively, and the total number of cycles is 2000 times, thereby preparing a layer of TiO2 with a thickness of 60nm on the surface of the substrate coated with CrAlN. A film with a structure of "CrN-CrAlN-TiO2" is obtained on the surface of the substrate.

[0135] After testing, the internal stress of the film with the structure of "CrN-CrAlN-TiO2" prepared in comparative example 2 is 175MPa. The film anti-peeling test results show that the film on the surface of the sample is slightly damaged and peeled off.

[0136] In Comparative Example 1, the single-layer TiO2 film failed to effectively achieve the anti-coking protection function. In Comparative Example 2, although the "CrN-CrAlN" composite layer was added to the film and the film stress was effectively reduced, breakage and peeling still occurred. In contrast, the low-stress alternating laminated films prepared in Examples 1 to 4 showed anti-coking protection performance that was significantly better than that of the comparative experiment, successfully avoided breakage and peeling, and had better stability and durability. Therefore, the low-stress alternating laminated film of the present invention not only performs well in the anti-coking protection function, but also has obvious advantages in improving the long-term durability and reliability of the film.

[0137] The present invention forms an alternating laminated film by multiple depositions. Specifically, a CrN transition layer, a CrAlN hard layer and a TiO2 anti-coking functional layer are first deposited on the substrate surface in sequence to form a first layer of alternating laminated structure; then the same "CrN-CrAlN-TiO2" layer is deposited again on the basis thereof, thereby achieving a multi-level, alternating arrangement of the film. This dual deposition strategy effectively optimizes the internal stress distribution of the film, significantly reduces the internal stress of the overall film through mutual compensation of interlayer stress, thereby improving the adhesion, anti-stripping and high-temperature stability of the film, and further enhancing the anti-coking performance of the intake and exhaust valves.

[0138] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0139] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A low stress anti-coking alternately laminated film for engine intake and exhaust valves, characterized in that: The invention comprises a CrN film, a CrAlN film, a TiO2 film, a CrN film, a CrAlN film and a TiO2 film which are sequentially arranged on a substrate from bottom to top.

2. The low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 1, characterized in that: The thickness of CrN films is 0.2 to 0.5 μm; The thickness of CrAlN films is 2 to 4 μm; The thickness of TiO2 film is 50-150nm.

3. The low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 1, characterized in that: The total thickness of the low stress anti-coking alternately laminated film is 5 to 9 μm.

4. A method for preparing a low-stress anti-coking alternately laminated film for engine intake and exhaust valves, characterized in that: The following steps are involved: A CrN film is first deposited on the substrate surface, a CrAlN film is deposited on the CrN film, and a TiO2 film is prepared on the CrAlN film; A CrN film is deposited on a TiO2 film, a CrAlN film is deposited on a CrN film, and a TiO2 film is prepared on a CrAlN film to obtain a low-stress anti-coking alternating laminated film for an engine intake and exhaust valve.

5. The method for preparing a low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 4, characterized in that: The thickness of CrN films is 0.2 to 0.5 μm; The thickness of CrAlN films is 2 to 4 μm; The thickness of TiO2 films is 50 to 150 nm; The total thickness of the low stress anti-coking alternately laminated film is 5 to 9 μm.

6. The method for preparing a low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 4, characterized in that: The preparation process of CrN film is as follows: using Cr target, the multi-arc ion plating process parameters are: arc current is 70-100A, deposition bias is 100-300V; the chamber pressure is 1-5Pa, the nitrogen flow rate is 1300-1500sccm, and the deposition temperature is 350°C.

7. The method for preparing a low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 6, characterized in that: The CrAl target is an alloy target in which the atomic percentage of Cr is 60% to 75%.

8. The method for preparing a low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 4, characterized in that: The preparation process of CrAlN film is as follows: using CrAl target, the multi-arc ion plating process parameters are: arc current is 70-100A, bias voltage is 50-80V, chamber pressure is 1-5Pa, nitrogen flow rate is 1300-1500sccm, and deposition temperature is 350°C.

9. The method for preparing a low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 4, characterized in that: The process for preparing TiO2 thin film is as follows: titanium isopropoxide is used as the titanium source precursor and hydrogen peroxide is used as the oxygen source. Nitrogen is used as the purge gas in a single cycle of the atomic layer deposition process. The times for titanium source precursor injection, nitrogen purge, oxygen source injection, and nitrogen purge are 1 to 2 s, 25 to 35 s, 0.1 to 0.3 s, and 20 to 35 s, respectively. The total number of cycles of the atomic layer deposition process is 2000.

10. The method for preparing a low stress anti-coking alternately laminated film for engine intake and exhaust valves according to claim 9, characterized in that: The temperature of the titanium source precursor is 70-90°C, the temperature of the coating area is 200-250°C, the background vacuum is lower than 50mtorr, and the nitrogen purge working pressure is 100-200mtorr.

Citation Information

Patent Citations

  • Coating material for parts of engine exhaust system and method for manufacturing the same

    CN103707568A

  • Inorganic high-temperature-resistant low-infrared-emissivity composite coating and preparation method thereof

    CN104149410A

  • Surface anti-coking nano composite thin film and preparation method thereof

    CN109468614A

  • High-temperature-resistant anti-coking chromium-aluminum-nitrogen / titanium dioxide composite coating and preparation method thereof

    CN113584440A

  • CrAlN coating of PCB milling cutter and processing method of CrAlN coating

    CN114959574A